2007
DOI: 10.1159/000099176
|View full text |Cite
|
Sign up to set email alerts
|

Lymph Node Clearance after Total Mesorectal Excision for Rectal Cancer: Laparoscopic versus Open Approach

Abstract: Background: Laparoscopic resection of the rectum is still under scrutiny for its adequacy of oncological clearance. Aim: To assess lymph node yield after laparoscopic total mesorectal excision (TME) for rectal cancer as compared to the open approach. Methods: 74 patients with middle and low rectal cancer were prospectively randomized in two groups. Group A included 39 patients who had an open TME (35 with low anterior resection of the rectum (LARR) and 4 with abdominoperineal resection of the rectum (APR)). In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0
9

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 53 publications
(27 reference statements)
2
43
0
9
Order By: Relevance
“…For rectal cancer, 9 phase III randomized clinical trials 11,20,21,[33][34][35][36][37][38][39][40][41][42] and 7 meta-analyses were selected. 28,29,[43][44][45][46][47] No meeting abstracts satisfied the inclusion criteria.…”
Section: Researchmentioning
confidence: 99%
“…For rectal cancer, 9 phase III randomized clinical trials 11,20,21,[33][34][35][36][37][38][39][40][41][42] and 7 meta-analyses were selected. 28,29,[43][44][45][46][47] No meeting abstracts satisfied the inclusion criteria.…”
Section: Researchmentioning
confidence: 99%
“…Pechlivanides G, et al has shown in their study that laparoscopic resection of the rectum can achieve similar lymph node clearance to the open approach (8).…”
Section: Discussionmentioning
confidence: 92%
“…In most of the studies it is proven that the resection is comparable with open surgery achieving acceptable oncological requirements (7,8) whilst providing benefits of reduced morbidity (1-7). The criteria to assess oncologically acceptable resection, is the number of lymph nodes harvested and tumour free distal resection margin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the successful introduction of laparoscopic colectomy by Jacobs et al [1] , laparoscopic surgery, especially laparoscopic rectal surgery has been developed considerably [2][3][4][5][6] . Laparoscopic total mesorectal excision (TME) for rectal cancer whether hand-assisted, laparoscopy-assisted or robotic-assisted laparoscopic technique can offer advantages over open TME, such as greater comfort and an earlier return to daily activities while preserving the oncologic radicality of the procedure [7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%